DE L’ÉCRITURE DE SOI À L’AUTOTHÉORIE : « LE FRIGIDAIRE EST VIDE. ON PEUT LE REMPLIR » DE CHANTAL AKERMAN - Andrei LAZAR (Studia Universitatis Babeş-Bolyai. Philologia)
From Self-Writing to Autotheory: “Le frigidaire est vide. On peut le remplir” by Chantal Akerman. Chantal Akerman’s work is characterised by her ability to merge different artistic forms such as cinema, writing and contemporary art installations. These allow her to question her own identity, her family heritage and her status as a filmmaker, in a creative freedom that reflects her opposition to generic conventions and affirms her openness to experimentation. “Le frigidaire est vide. On peut le remplir” is an autotheoretical work, as Lauren Fournier defines it, incorporating elements of feminism, intersectionality, and a reflection of concepts emerging from Barthes, Deleuze, Freud and Lacan. This transdisciplinary approach is doubled by an intermedial one, since this autobiographical narrative is revisited and modified as part of a contemporary art installation that also reiterates and questions the autotheoretical elements of her work.